2007
DOI: 10.1002/jclp.20427
|View full text |Cite
|
Sign up to set email alerts
|

Christian religious functioning and trauma outcomes

Abstract: While some trauma survivors find their faith helpful in recovery, others find it a source of distress, and still others abandon their faith. More complex conceptualizations of religious functioning are needed to explore its relationship with trauma. This study explores such relationships using measures of religious action and behaviors in a community sample of 327 church-going, self-identified trauma survivors. A principal components analysis of positive and negative religious coping, religious comforts and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
121
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(133 citation statements)
references
References 43 publications
10
121
0
2
Order By: Relevance
“…In sum, while higher PRC is associated with greater well-being, it is not consistently inversely linked to poorer functioning. As an example, in a study of 327 church-going, self-identified trauma victims, PRC was positively related to post-traumatic growth (r = 0.37), but unrelated to PTSD symptoms [45].…”
Section: Concurrent Validitymentioning
confidence: 99%
“…In sum, while higher PRC is associated with greater well-being, it is not consistently inversely linked to poorer functioning. As an example, in a study of 327 church-going, self-identified trauma victims, PRC was positively related to post-traumatic growth (r = 0.37), but unrelated to PTSD symptoms [45].…”
Section: Concurrent Validitymentioning
confidence: 99%
“…Those who view their spirituality, faith community, and/or Higher Power as sources of support, validation, and acceptance are more able to make healthy meanings and recover than those who don't. Those who view their spirituality, faith community, and/or Higher Power as sources of judgment, punishment, or rejection have difficulty recovering from trauma (Elliott, 1994;Falsetti, Resick, & Davis, 2003;Fitchett, Rybarczyk, Demarco, & Nicholas, 1999;Fontana & Rosenheck, 2004;Harris et al, 2008b;Pargament, Koenig, Tarakeshwar, & Hahn, 2004;Strawbridge et al, 1998). This research suggests that using spiritually integrated interventions could help trauma survivors to more effectively use their spiritual practices and beliefs to deal with trauma and thus foster recovery.…”
mentioning
confidence: 91%
“…Negative religious coping challenges these positive answers to stressful life events showing, for example, punishing reappraisal (the feeling God is punishing the person for their sins) or spiritual discontent. In this respect, positive religious coping strategies were found to be beneficial, whereas negative religious coping resulted in poorer psychological adjustment to stress [2,3,4]. …”
Section: Introductionmentioning
confidence: 99%